The Academic Takes it All? A Comparison of Returns to Investment in Education between Graduates and Apprentices in Canada - Susanne Kopatz; Matthias Pilz (International Journal for Research in Vocational Education and Training (IJRVET), 2015)
This paper analyses the returns to education of specific occupations in Canada. The purpose is to scrutinize whether and in how far academic and vocational education do differ in monetary benefits regarding individual returns. Therefore, two different methodologies of calculation are used to compute the concrete returns to education. As a result it is shown empirically that within the here selected occupational groups (e.g. librarians and electricians) there is no decisive earnings benefit regarding academic careers, although a positive correlation of income level and educational achievement can be verified. Our findings justify revisiting the underlying assumption that vocational education and training cannot generate benefits comparable with those generated by higher education. The earnings data suggest that monetary aspects may be less crucial than generally assumed to the reputation and perceived value of vocational education and training. Therefore, social status and prestige seem to be the most significant contributory factors to vocational training's low status in Canada.
Keywords: 330; Returns to Education; Educational Economics; Investment in Education; Canada; Vocational Education and Training; Graduation; Individual Returns; Occupations